1998
DOI: 10.1086/311310
|View full text |Cite
|
Sign up to set email alerts
|

Complex Velocity Fields in the Shell of T Pyxidis

Abstract: We present spatially-resolved, moderate-resolution spectrophotometry of the recurrent nova T Pyx and a portion of the surrounding shell. The spectrum extracted from a strip of width 10'' centered on the star shows well-known, strong emission lines typical of old novae, plus a prominent, unfamiliar emission line at 6590 Angstroms. This line, and a weaker companion at 6540 Angstroms which we also detect, have been previously reported by Shahbaz et al., and attributed to Doppler-shifted H alpha emission from a co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Steeghs & Casares 2002), where it is thought to be produced by a fluorescence process as the front side of the donor is strongly irradiated by the hot accretor. The Bowen blend was clearly visible in the spectrum of T Pyx obtained by Margon & Deutsch (1998), and based on this, we were hoping to detect narrow components associated with the donor. However, no narrow donor star features were found in the blend.…”
Section: Discussionmentioning
confidence: 88%
“…Steeghs & Casares 2002), where it is thought to be produced by a fluorescence process as the front side of the donor is strongly irradiated by the hot accretor. The Bowen blend was clearly visible in the spectrum of T Pyx obtained by Margon & Deutsch (1998), and based on this, we were hoping to detect narrow components associated with the donor. However, no narrow donor star features were found in the blend.…”
Section: Discussionmentioning
confidence: 88%
“…In many recent novae -including T Pyx -this material produces a detectable, line-emitting "nova shell" around the system. Following up on the announcement of Shahbaz et al (1997), O'Brien andCohen (1998) and Margon and Deutsch (1998) obtained spatially resolved spectroscopy of T Pyx and its nebula. These observations showed that the "jet lines" identified by Shahbaz et al are, in fact, nebular [N ii] lines associated with the nova shell.…”
Section: Do Cataclysmic Variables Launch Jets? Motivation and Backgroundmentioning
confidence: 99%
“…From the comparison of the size of the nebula at different epochs, they derived an upper limit of about only 40 km s −1 (but assumed d = 1500 pc) on the systematic expansion velocity of the knots. Instead, both Margon &Deutsch (1998) andO'Brien &Cohen (1998), in a study of the alleged jet components in the Hα line (Shabaz et al 1997), identified these features as due to the [NII] 6548, 6584 lines and interpreted their wavelength shifts as produced by an expansion velocity of about 500 km s −1 along the line of sight through the center of the shell. If some of these "variable knots" happen to lie within the IUE PSF they may also explain the emission line changes and the unusual spectroscopic signatures in the UV spectrum of T Pyx.…”
Section: ) the (Irradiated) Chromosphere Of The M Dwarf Companionmentioning
confidence: 99%
“…Shabbaz et al (1997) interpreted the presence of two spectral features on either side of Hα as the signature of a bi-polar, highvelocity, highly collimated jet, but subsequent studies by Margon & Deutsch (1998) and by O'Brien & Cohen (1998) have shown that these features are instead emission in the [NII] 6548 and 6584 lines from a complex velocity field in the surrounding shell.…”
Section: Introductionmentioning
confidence: 99%